Effect of different axial speed patterns on cyclic fatigue resistance of rotary nickel-titanium instruments - Myint Thu; Arata Ebihara; Keiichiro Maki; Miki Nishijo; Shunsuke Kimura; Taro Nakatsukasa; Moe Sandar Kyaw; Takashi Okiji (BMC, 2022)
Abstract Background To evaluate the effect of pecking motions with faster upward speed on the dynamic cyclic fatigue resistance of nickel-titanium rotary instruments with different metallurgy. Methods Forty each of ProTaper Universal F3 (PTU) and ProTaper Gold F3 (PTG) instruments (size #30/.09) were equally divided into four groups. The test was performed using an 18-mm-long stainless steel artificial canal with a 5-mm radius of curvature, a 45° canal curvature and a 2-mm canal diameter. A downward speed of 100 mm/min was employed, while the upward speed was set at 100, 150, 200 or 300 mm/min. Time to failure (Tf), number of cycles to failure (Nf) and number of pecking motions to failure (Np) were recorded. Statistical analysis was performed using Kruskal Wallis and Mann-Whitney U tests for Tf, Nf, and Np (α = 0.05). Results The 100/300 mm/min group showed significantly higher Np values than the 100/100 mm/min group (p < 0.05), whereas there were no significant differences in Tf and Nf among the tested speed groups (p < 0.05) in either PTU or PTG. PTG exhibited significantly higher Tf, Nf, and Np than PTU (p < 0.05). Conclusions Under the tested conditions, the fastest upward speed group showed significantly higher cyclic fatigue resistance, as demonstrated by larger Np, than the same speed group. PTG had significantly higher cyclic fatigue resistance than PTU in all groups.